ANALYSIS OF PROBLEMS OF IMPLEMENTATION OF THE PRIORITY DIRECTION OF «PERSONALIZED MEDICINE» IN THE FORMAT OF FULL PROJECT CYCLE - A. N. Petrov; N. G. Kurakova; I. M. Son (Ekonomika Nauki)
On an example of a priority direction «the personalized medicine», allocated by Strategy of scientific and technological development of the Russian Federation, risks and barriers of realization of projects of a full cycle are examined. Approaches to design and examination of complex scientific and technological projects and to the system of their analytical support are offered. The importance of identifying a qualified customer for full-cycle projects, in the capacity of which either the FEI or a large company interested in developing the priority direction can act, has been substantiated. It was recommended to delegate to a qualified customer the authority to formulate a full cycle project architecture. To minimize and manage a wide range of risks and barriers, that pose a threat to the implementation of all phases of such projects, a multi-parameter expertise is needed, along with an analysis of the trends in the development of a new technology direction, an assessment of economic feasibility, personnel and infrastructure support, adequacy of legal regulation.